2018
DOI: 10.1016/j.resuscitation.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia outcome prediction after extracorporeal life support for hypothermic cardiac arrest patients: The HOPE score

Abstract: In this large retrospective study we found that our score was superior to dichotomous triage based on serum potassium level in assessing which hypothermic patients in cardiac arrest would benefit from extracorporeal life support. External validation of our findings is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
173
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(193 citation statements)
references
References 38 publications
11
173
1
8
Order By: Relevance
“…Based on a retrospective analysis of 286 patients in 18 publications, Pasquier et al developed the HOPE score, which takes into account six clinico-biological variables who are age, gender, asphyxia associated, CPR duration, serum potassium level and temperature (score calculation and predicted survival use an algorithm which is available online at: www.hypothermiascore.org). The statistical analysis showed that the area under the ROC curve for the HOPE score is more useful than kalaemia for predicting survival [12]. Saczkowski et al published an another review screening 658 patients from 40 clinical cases and 44 retrospective cohorts.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a retrospective analysis of 286 patients in 18 publications, Pasquier et al developed the HOPE score, which takes into account six clinico-biological variables who are age, gender, asphyxia associated, CPR duration, serum potassium level and temperature (score calculation and predicted survival use an algorithm which is available online at: www.hypothermiascore.org). The statistical analysis showed that the area under the ROC curve for the HOPE score is more useful than kalaemia for predicting survival [12]. Saczkowski et al published an another review screening 658 patients from 40 clinical cases and 44 retrospective cohorts.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…However, the lactate level was high, and the pH was below 7, which did not prevent good clinical and neurological outcomes. HOPE and ICE scores were not available when we managed our patient but if we calculated them, the HOPE score resulted in 59% survival, and the ICE score was 0 (0 point for male sex, 0 point for no associated asphyxia and 0 point for the initial serum potassium concentration less than 5 mmol/l), corresponding to a probability of survival with a good neurological outcome of 60% [12,13]. These results, similar for the two predictive scores, raise the question of their usefulness in clinical practice.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…For instance, a person who drowns in very cold water may have a good chance for meaningful recovery if ECMO cannulation occurs promptly. However, duration of CPR while traveling to the nearest ECMO center impacts the chance for neurologically intact survival (Pasquier et al 2018). A person who is closer to an ECMO center not only has a better chance of receiving ECMO but has a better chance that such treatment will be successful.…”
Section: Mayo Clinicmentioning
confidence: 99%
“…In view of these limitations, a new multivariable score to predict survival after extracorporeal life support rewarming in hypothermic patients with cardiac arrest was recently published. 2 The Hypothermia Outcome Prediction After ECLS score is a promising new tool in modern hypothermia management. Its accuracy to predict survival with extracorporeal life support rewarming after hypothermic cardiac arrest was superior to a potassium-based prediction.…”
Section: Hypothermic Cardiac Arrest Patients' Selection Criteria For mentioning
confidence: 99%
“…Its accuracy to predict survival with extracorporeal life support rewarming after hypothermic cardiac arrest was superior to a potassium-based prediction. 2 The score includes the following 6 clinical variables determined at hospital admission: age, sex, hypothermia with or without asphyxiation, CPR duration, core temperature, and serum potassium level (online calculator available at http://www.hypothermiascore.org).…”
Section: Hypothermic Cardiac Arrest Patients' Selection Criteria For mentioning
confidence: 99%